Central Atrophy Early in Multiple Sclerosis: Third Ventricle Volumetry versus Planimetry. Issue 3 (28th November 2016) - Lutz, Theodor; Bellenberg, Barbara; Schneider, Ruth; Weiler, Florian; Köster, Odo; Lukas, Carsten
ABSTRACT: BACKGROUND AND PURPOSE: Cerebral atrophy has been suggested to be a reliable magnetic resonance imaging (MRI) predictor of subsequent disability in all stages of multiple sclerosis (MS). However, no accepted methodology for routine clinical use exists to date. We sought an easy to apply and fast technique to evaluate cerebral ventricular volume in patients with MS with similar accuracy as a semiautomatic volumetric method. METHODS: The study included 104 patients, 61 diagnosed with MS and 43 with clinically isolated syndrome. In addition, 30 healthy controls were enrolled. Physical disability was assessed with the expanded disability status scale and cognitive disability with the Multiple Sclerosis Inventory Cognition (MUSIC) test. All subjects received standardized 3‐dimensional (3D) MR‐imaging on a 3 T scanner. Third ventricle volume (3VV) was obtained from 3D T1‐weighted images using a semiautomated technique, and compared against planimetric assessment of the width of the third ventricle aligned (a3VW) and unaligned (u3VW) to anatomical landmarks. RESULTS: a3VW was obtained within seconds with excellent intra‐ and interrater agreement, and outperformed volumetric measurements regarding the differentiation of MS patients from healthy controls. a3VW had the strongest correlations with 3VV ( r = .78, P < .001) and showed moderate inverse correlation with MUSIC cognition score ( r = −.310, P < .005). CONCLUSIONS: a3VW is a time‐effective and robust biomarker that has strong correlations with volumetric measurements and can be established as standard in the MRI quantification of central brain atrophy in patients with early MS.